Regulation of Rho GTPases in the Vasculature by Cullin3-Based E3 Ligase Complexes - Podieh, Fabienne; Hordijk, Peter L. (Frontiers in Cell and Developmental Biology, 2021)
Cullin3-based ubiquitin E3 ligases induce ubiquitination of substrates leading to their proteasomal or lysosomal degradation. BTB proteins serve as adaptors by binding to Cullin3 and recruiting substrate proteins, which enables specific recognition of a broad spectrum of targets. Hence, Cullin3 and its adaptors are involved in myriad cellular processes and organ functions. Cullin3-based ubiquitin E3 ligase complexes target small GTPases of the Rho subfamily, which are key regulators of cytoskeletal dynamics and cell adhesion. In this minireview, we discuss recent insights in Cullin3-mediated regulation of Rho GTPases and their impact on cellular function and disease. Intriguingly, upstream regulators of Rho GTPases are targeted by Cullin3 complexes as well. Thus, Rho GTPase signaling is regulated by Cullin3 on multiple levels. In addition, we address current knowledge of Cullin3 in regulating vascular function, focusing on its prominent role in endothelial barrier function, angiogenesis and the regulation of blood pressure.